Sexual behaviors and associated factors among first-year undergraduates at overseas Chinese-oriented universities in China - Chen, Zulin; Zheng, Yikun; Lin, Lihan; Chen, Yongjun; Zheng, Yunting; Chen, Hongmiao (Frontiers in Public Health, 2025)
BackgroundThis study aims to analyze the status of sexual behavior and its influencing factors among first-year undergraduate students in Chinese overseas Chinese schools, providing scientific evidence for university sexual health education and public health interventions. It also explores sexual behavior patterns and prevention strategies in a multicultural context.MethodsA cluster sampling method was employed to conduct a questionnaire survey among the 2024 cohort of freshmen at Huaqiao University (n = 4,892) in October 2024. The questionnaire covered basic sociodemographic characteristics, knowledge about HIV and Monkeypox prevention, and sexual behavior. Chi-square tests and binary logistic regression models were used to analyze differences in sexual behavior among students with different characteristics and main influencing factors.ResultsThe study found that the sexual behavior occurrence rate among students was 6.6%. Sensitivity analyses were conducted to verify the robustness of key associations. The rate was significantly higher among students from Hong Kong, Macau, and Taiwan compared to those from Mainland China and abroad (p < 0.05), which was corroborated by the logistic regression (OR = 3.737, 95% CI: 2.846–4.908). Students with higher knowledge about Monkeypox had a higher occurrence of sexual behavior (OR = 1.174, 95% CI: 1.060–1.301). Students who were aware of the consequences of homosexual behavior had a significantly lower occurrence of sexual behavior (OR = 0.453, 95% CI: 0.346–0.594). Compared with those who opposed homosexual behavior, students with neutral and supportive attitudes toward homosexual behavior had a lower occurrence of sexual behavior (OR = 0.377, 95% CI: 0.287–0.496; OR = 0.371, 95% CI: 0.218–0.629). Students who received HIV prevention services in the past year had a lower occurrence of sexual behavior (OR = 0.294, 95% CI: 0.213–0.405). In comparison, those who participated in HIV awareness services in the past year had a higher occurrence of sexual behavior (OR = 4.280, 95% CI: 3.140–5.834). All associations remained robust in sensitivity analyses.ConclusionThe occurrence rate of sexual behavior among first-year students in Chinese overseas Chinese schools is relatively low, but significant differences are observed based on region of origin, gender, and knowledge level. The study indicates that sexual health education should focus on students’ cultural background, gender roles, and cognitive differences, combining behavioral interventions to enhance the relevance and effectiveness of education and reduce high-risk sexual behaviors.